1994
DOI: 10.1017/s0007485300032181
|View full text |Cite
|
Sign up to set email alerts
|

Migrating moths collected in tower-mounted light traps in northern New South Wales, Australia: influence of local and synoptic weather

Abstract: Catches of moths in tower-mounted light traps in northern New South Wales were analysed in relation to local and synoptic weather. Catches were correlated with windspeed, relative humidity and possibly rainfall. No correlations were obtained with temperature or moon phase. Catches were more likely to occur when winds were from the east, and were associated with wind shifts. There was a significant association with the passage of depressions or troughs, but not cold fronts. The traps were considered to be poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…In every investigated forest stand, one trap was fixed on a 1.80-m-high metal gibbet. The operation of the light traps within the (Gregg et al, 1994;Steinbauer, 2003). As a consequence, the synchronous operation of light traps is necessary for a legitimate comparison of moth catches from different biotopes (Intachat et al, 1997).…”
Section: Light Trap Methodsmentioning
confidence: 99%
“…In every investigated forest stand, one trap was fixed on a 1.80-m-high metal gibbet. The operation of the light traps within the (Gregg et al, 1994;Steinbauer, 2003). As a consequence, the synchronous operation of light traps is necessary for a legitimate comparison of moth catches from different biotopes (Intachat et al, 1997).…”
Section: Light Trap Methodsmentioning
confidence: 99%
“…Gregg et al (1994) found reduced catches of migratory moths when wind speed increased, as did Edwards et al (1987) for Culicoides midges. Gentle rain may not reduce catches but heavy rain and moderate or strong winds do so.…”
mentioning
confidence: 85%
“…The wind force was significantly negatively correlated with light trap catches of N. lugens. Wind generally affects catch size, that is, a significantly negative correlation exists between total moth catch and wind speed (Gregg et al 1994). In addition, catches of insect species may be increased by placing windshields on the windward side of the traps (Hollingswort et al 1961).…”
Section: Effect Of Weather Factors On the Trap Catches Of Rice Planthmentioning
confidence: 99%